PEMBUATAN VIDEO PEMBELAJARAN MATERI KESEHATAN RUMAH DAN LINGKUNGAN PADA KEAHLIAN ILMU KELUARGA - Annida Jihadiyyah Nur'azizah, - (2020)
Learning Video is one of the media that can help students to understand a home and environmental health theory on family science skills. The purpose of this research is to make video learning of home and environmental health in family sciences, and then validated to know the feasibility of learning media. The method that used in this research is R&D (Research and Developement). Then it applied through the development of Planning, Production, Evaluation (PPE) model according to Richey and Klein (2007), which was adjusted to the needs of researchers. The general research step is the planning of a video product; Video creation (shooting and editing); Product evaluation by theory and media experts. Findings on this study stated that after validation by theory experts, the material on learning videos is reasonably feasible with poorly structured and comprehensive material records, and there are some materials that need to be added to comply with the provisions. Further validation results of media experts state that videos are less feasible because the sound on learning videos must use human narrator with good and correct pronunciation, and the addition of material texts must be added. Related to this home and environmental health Learning video is that it will be better to complete the completion of the study media that is implemented for the students so that their usefulness can be felt.